Consumptive Behavior and Self-Efficacy towards Financial Management with Financial Literacy as an Intervening Variable - Irma Setyawati (Budapest International Research and Critics University, 2022)
The crucial objective of this research is to measure the impact of consumptive behavior, self-efficacy and financial literacy on people's financial management. This research technique is qualitative research. The population of this research is young workers in Bandung with purposive sampling technique with the acquisition of 32 questionnaire data samples. The benchmark used is male or female, aged 17-35 years, already working, and domiciled in Bandung. The results of the study show that consumptive behavior has no positive effect on financial management. Self-efficacy has a positive effect on financial management and self-efficacy on financial management with financial literacy as an intervening variable has a positive influence on young workers in Bandung.